The influence of El-Nino on microclimate change and soil water content in Gambung tea plantation - Rezamela, Erdiansyah; Dalimoenthe, Salwa Lubnan (Jurnal Penelitian Teh dan Kina, 2016)
The very strong intensity of 2015 El-Nino affected on microclimate change and soil water content of Gambung Tea Plantation. The observation results indicated that in the year of 2015 Gambung was experienced four dry months (with rainfall <60 mm), with maximum air temperature 30,8ÂºC and air humidity dropped to 65%. These condition were not suitable for tea plant to grow well, which normally required two dry months at minimum (rainfall < 60 mm), air temperature of 18â25ÂºC, and with relative humidity of above 70%. The affected areas by drought were present in a map (see Figure 3 of the text). About 65% of the total blocks (north section about 80% and south section about 50%) of Gambung tea plantation were affected by drought. The worst affected were blocks A6 (north section) and B8 (south section). In these blocks, about 54.70% of plant were in normal growth condition; 14.65% were in temporary and permanent wilting status; 25.34% in the state of dropping their leaves; 5.19% of the plants with dried buds twigs, and 0.12% with dried twigs and dried old branches. The soil water content (at 10 cm depth) in these blocks dropped to 7.02% and 4.99% from normally required at minimum 30%.